Prácticas co-creativas. Decolonizar la naturaleza - Yeregui, Mariela (Artelogie. Recherche sur les arts, le patrimoine et la littérature de l'Amérique latine, 2017)
El diálogo arte-tecnología en América Latina pone en foco litigios recurrentes: ¿tecnologías sustentadas por los discursos legitimantes de la modernidad o paradigmas diferentes y periféricos en la asunción e ideación de tecnologías en el contexto del arte? ¿Qué sucede con las prácticas que incorporan elementos biológicos, habitualmente uniformizadas bajo la categoría de “bioarte”? Las prácticas artísticas tecnológicas en Argentina en los últimos diez años alumbran zonas de pensamiento y praxis que ameritan ser revisadas: el diálogo arte/naturaleza desde perspectivas no-antropocéntricas, la configuración de discursos en los que subyacen representaciones, miradas y prácticas que se apartan de cánones normalizados y, por último, operaciones disruptivas en lo que respecta a los algo usuales criterios de funcionalidad, utilitarismo y efectismo tecnológico.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Artistes afro-brésiliennes, d’un siècle à l’autre - Giunta, Andrea (AWARE : Archives of Women Artists, Research and Exhibitions, 2021)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Postcolonial/Décolonial: La preuve par l'art - Toussaint, Évelyne (Presses universitaires du Midi, 2021)
"Les liens entre l'art contemporain et les questions de colonialité, postcolonialité, et décolonialité sont anciens et multiples. Des artistes occidentaux et non-occidentaux, depuis plusieurs décennies déjà, s'en sont emparés pour produire des œuvres qui témoignent de leurs engagements politiques, sociétaux et esthétiques. Des concepts que les études postcoloniales ont approfondies ou inventées – agency (agentivité), mimicry (mimétisme/simulacre), ou essentialisme stratégique –, en autant d'outils utiles à démêler la complexité des relations coloniales et, au-delà, de toutes les relations de domination, sont ainsi revisités par les artistes. D'autre part, des auteurs, relevant de ces champs d'études qui conservent aujourd'hui toute leur actualité politique et leur pertinence théorique, disent à leur tour l'intérêt qu'ils portent à la création contemporaine. Associant vingt historiens de l'art et chercheurs en littérature, philosophie, droit ou psychanalyse, Postcolonial/Décolonial. La preuve par l'art présente des travaux portant sur des démarches artistiques (Betye Saar, Fred Wilson, Sarkis, Lidwien van de Ven, Voluspa Jarpa, des artistes du collectif Mira au Mexique, Iris Kensmil, Jean Renoir, et bien d'autres), mais aussi sur des propositions institutionnelles (notamment initiées par le Centro de Arte y Comunicación de Buenos Aires, la Biennale de Venise ou le Van Abbemuseum d'Eindhoven), associées en de nouveaux réseaux de solidarités. Une place particulière est réservée aux singularités artistiques, théoriques et juridiques en Amérique latine, lieu d'émergence des théories décoloniales. Sous un angle historiographique et épistémologique, on trouvera ici des analyses des fondements historiques, théoriques et idéologiques du postcolonial dont les théorisations, loin de la saturation conceptuelle dont certains veulent les accuser, concernent particulièrement l'histoire de l'art. "
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous Cinema in Expansion: Challenges and Promises of an Intercultural Relationship - Frey, Aline; Brito, Thaís (Canadian Journal of Film Studies, 2020)
Les auteures dressent le portrait tant des défis actuels que des possibilités qui naissent des relations interculturelles se tissant entre commissaires et cinéastes autochtones et non-autochtones dans le cadre du plus grand festival du film autochtone du Brésil, Cine Kurumin. Ce festival annuel, fondé en 2011, se déroule dans des villages ruraux autochtones, de même que dans des métropoles brésiliennes, attirant ainsi des auditoires variés. Le festival est ouvert aux cinéastes autochtones et non-autochtones qui produisent du matériel audiovisuel portant sur des sujets autochtones de partout dans le monde. Divers processus créatifs y sont encouragés grâce à l’organisation d’ateliers de scénarisation, et des partenariats établis avec des chaînes de télévision permettent une plus large diffusion des films sélectionnés. Alors que les productions audiovisuelles autochtones se développent, leurs contenus se diversifient ; elles englobent en effet de plus en plus de thèmes et de styles, de formats et de perspectives variées. En s’appuyant sur un cadre théorique postcolonial et décolonial, les auteures proposent de nouvelles perspectives sur un cinéma en pleine expansion ; les réalisateurs autochtones et leurs films circulent de plus en plus au sein de festivals non thématiques, reçoivent des prix et font rayonner leurs propres voix et points de vue auprès de publics variés, ce qui crée de nombreuses possibilités d’interactions et de dialogues interculturels. En outre, la mise sur pied de Cine Kurumin témoigne du pouvoir des productions audiovisuelles autochtones de générer des relations interculturelles entre cinéastes, commissaires et public.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

WàCOLETIVO : Broderie, couture et crochet comme art contemporain dans l'espace public - WàCOLETIVO (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Musee Migrant – MuMi - Clériga Morales, Deyanira; Valenzuela Arámburo, Pável; Ledón Pereyra, Aldo Jorge (revue Periferias, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

L’art périphérique montre l’afro-diaspora en environnement digital - del Rei, Mariana (revue Periferias, 2021)
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Pour un féminisme afro-latino-américain - Gonzalez, Leila (Revue d'Études Décoloniales, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Introduction de feminismos desde abya yala - Gargallo, Francesca (Revue d'Études Décoloniales, 2020)
Quand les conditions requises pour le dialogue ne sont pas réunies, il est difficile d’expliquer à une femme blanche : " écoute, nous ne voulons pas qu’on nous impose des de critères féministes hégémoniques " . Cela étant, je reconnais et j’apprécie tout ce que j’ai appris sur les différents courants féministes. Car grâce à eux, je me reconnais comme sujette épistémique et je peux me penser à partir du corps et de l’espace où je vis. Ou encore tisser des idées féministes. C’est ainsi que la construction consciente de mon identité féministe communautaire se renforce et en même temps, nous contribuons au mouvement féministe dans le monde. Par exemple, l’une des étapes que nous devons franchir passe par la langue : nommer dans nos propres langues, qui auront été libérées, les catégories et les concepts que nous élaborons pour analyser l’oppression subie par notre peuple dans l’histoire et notre libération en tant que femmes indigènes, autochtones, paysannes, rurales, ou villageoises. Francesca Gargallo est une écrivaine et féministe autonome italo-mexicaine. Licenciée en philosophie de la Sapienza de Rome et docteure en Études Latinoaméricaines de l’UNAM mexicaine, cette spécialiste de l’histoire des idées féministes, prenant acte de l’échec de l’utopie socialiste, propose de chercher des alternatives à partir d’un féminisme clairement antiraciste, qui fasse la critique de l’ eurocentrisme. Elle s’intéresse au concept de colonialisme interne de Pablo González Casanova, ou de Silvia Rivera Cusicanqui. Le livre dont nous traduisons deux extraits, Feminismos desde Abya Yala. Ideas y proposiciones de las mujeres de 607 pueblos en NuestraAmérica, a été publié en 2012 aux éditions Desde abajo.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

L’hybris du point zero. Science, race et Lumières en Nouvelle-Grenade (1750-1816) - Castro-Gómez, Santiago (Revue d'Études Décoloniales, 2017)
Ce texte est la traduction de l’introduction au livre de Santiago Castro-Gómez, La hybris del punto cero: ciencia, raza e ilustración en Nueva Granada (1750-1816), Bogota: Ed. Pontificia Universidad Javeriana, 2005.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Féminismes et artivisme dans les Amériques, XXe-XXIe siècles - Quiroz, Lissell (Presses universitaires de Rouen, 2021)
"Y la culpa no era mia, ni donde estaba, ni como vestia", chantaient des femmes aux yeux bandés dans différentes villes d'Amérique latine en novembre 2019. Cette performance, créée par le collectif féministe Las Tesis, a fait le tour du monde. Elle montre la force et la vitalité de l'artivisme dans les Amériques. Ce volume porte sur la diversité des théorisations et des mobilisations féministes du continent américain, très dynamiques historiquement et de plus en plus visibles depuis la fin du XXe siècle. Le féminisme des Amériques est pluriel et possède une généalogie propre. Les auteures s'attachent à décliner ses différentes formes : chicano, décolonial, lesbien, queer, entre autres. L'originalité des actions féministes de la région provient de la mobilisation politique de genres artistiques, qu'ils soient musicaux (rap, reggaeton), picturaux ou des arts visuels. Cet artivisme joue ainsi un rôle central dans les formes d'action du continent et ce volume présente leur diversité, leur richesse et leur force créatrice et politique."--Page 4 of cover.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Ensayos de crítica feminista en nuestra América - Mendoza, Breny (Editorial Herder, 2019)
El feminismo hegemónico latinoamericano entró en crisis en los años noventa por su creciente contubernio con el Estado liberal, así como por su práctica política carente de teoría. No supo cómo responder a los desaires de la izquierda masculinista y quedó intacto por los nuevos teóricos de la descolonialidad. Su acción y pensamiento no sólo se manifestaron profundamente colonizados por Occidente, sino que no encontraron una voz clara para entrar en diálogo con ciertas corrientes del feminimo latinoamericano que cuestionaron sus postulados de género, raza y heteronormatividad.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

La question de la colonialité du genre - Mendoza, Breny (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2019)
Au sein du tournant décolonial que la théorie féministe latino-américaine a commencé à prendre, un nouveau concept a émergé, qui pourrait constituer un changement de paradigme dans notre compréhension du genre. Il s'agit du concept colonialité du genre, forgé par la philosophe argentine Maria Lugones dans ses deux derniers articles : « Heterosexualism and the Colonial/ Modern Gender System » (2007) et, plus récemment, « Toward a Decolonial Feminism » (2010), article qui n'a pas encore été tra...
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Manuel Zapata Olivella, le muntu africain et la décolonisation des imaginaires et des épistémologies en Amérique Latine - Akassi, Clément Animan (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2019)
Ce travail vise à montrer deux choses. La première, c’est de saisir toute l’importance du tournant postcolonial/afro-décolonial dans la construction d’une contre-épistémologie propre au sujet culturel colonisé africain. En d’autres termes, pour le sujet colonisé, cette contre-épistémologie sert à décoloniser les imaginaires, à partir d’un questionnement de la colonialité de l’épistémologie et du savoir donnés pour universels par l’occident. La deuxième chose, c’est que ̶ à quelques mois de la commémoration du centenaire de la naissance du prolixe et polygraphe auteur africain-colombien Manuel Zapata Olivella (1920-2004) ̶ cet article puisse le situer à sa juste place. Celle d’un sujet culturel colonisé africain des Amériques dont l’abondante production culturelle et la pensée, portées et révolutionnées par le concept de Muntu africain, participent de la décolonisation des imaginaires et de l’épistémologie
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Crítica y descolonización: el sujeto colonial en la cultura latinoamericana - González-Stephan, Beatriz; Universidad Simón Bolívar (1992)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Charla | Estética afro Identidad, saberes y resistencia - Banrepcultural (2019)
En esta charla conversaremos sobre las luchas históricas por la reivindicación de los derechos del pueblo afro que están detrás de su estética, específicamente en dos de sus expresiones femeninas: el turbante afro y el pelo natural, los cuales han servido como elementos de resistencia para la pervivencia de las prácticas y costumbres ancestrales. Como parte de la exposición temporal del Museo del Oro 'A bordo de un navío esclavista, La Marie-Séraphique' (que se presentó en Bogotá del 7 de octubre de 2018 al 7 de abril de 2019) hablamos en el museo sobre algunos peinados ancestrales, como la espina de pescado, las tropas, el hundidito, el ciempiés y la vicha, y sobre los usos, significados y modelos de los turbantes afro, como la cadena del esclavo, la autoridad, el kitambala, el enkeycha y el doek. El termino mata ‘e pelo surge de las expresiones propias de nuestras ancestras, que se referían al pelo afro cómo una gran mata (árbol), frondosa, incontrolable y rizada, que requería unos cuidados particulares por su condición crespa, abundante y diversa. El cuerpo de la mujer negra, raizal y palenquera ha estado históricamente ligado a las luchas por la reivindicación de los derechos del pueblo afro, siendo la mata ‘e pelo el elemento estético que más las ha transmitido. Entre las personas de ancestros africanos, la estética del pelo afro se remonta a un pasado cargado de lucha y resistencia, pues las trenzas fueron usadas para la elaboración de mapas que marcaban el camino a la libertad de los cimarrones. Las mujeres se reunían en el patio para peinar a las más pequeñas. Diseñaban en su cabeza un mapa lleno de caminitos y salidas de escape, en el que ubicaban los montes, ríos y árboles más altos. Así, al verlas, los hombres sabían cuáles rutas tomar. Su código, desconocido para los amos, les permitía a los esclavizados huir. El balance humano de la trata de cautivos africanos a través del Atlántico es dramático: con una inmensa brutalidad, desplazó a 13 millones de hombres, mujeres y niños entre la segunda mitad del siglo XVI y finales del siglo XIX. #ElMuseoDelOroTambiénEsAfro Producción Banco de la República Realización Santiago Martínez
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Vistazo Crítico 135: Nelson Fory Ferreira: la historia nuestra caballero. - Arcos-Palma, Ricardo (VISTAZOS CRÍTICOS: 20 años de crítica de la cultura y del arte, 2015)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Presencia negra en Bogotá: Décadas 1940-1950-1960
La exposición Presencia negra en Bogotá hace parte de la investigación en Migraciones que desde la Universidad Nacional lideran Mercedes Angola y Maguemati Wabgou. Está presente en el Claustro de San Agustín, como un homenaje a los hacedores de grandes historias que se desconocen, personas cuyos aportes a la construcción de la sociedad colombiana y a la consolidación de la identidad nacional desde diversas perspectivas y disciplinas ha invisibilizado la historia colombiana. En compañía de sus protagonistas, acompáñenos en la formulación de nuevas preguntas de investigación en torno al aporte de la gente negra a Colombia y a países vecinos, pues no solo se ha producido migración interna sino, "fuga" hacia otros países. Invitados : Mercedes Angola, artista plástica e investigadora y Maguemati Wabgou, sociólogo e investigador.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

¡Mandinga sea! África en Antioquia - Luz Adriana Maya Restrepo; Raúl Cristancho (Universidad de los Andes, 2015)
Compuesta por 355 obras de arte de naturaleza muy variada, la exposición en sala y ahora impresa busca visibilizar, dignificar, valorar y difundir los legados civilizatorios, reativos, culturales, económicos, sociales, políticos, tecnológicos, ambientales e históricos de los pueblos del África occidental y de sus descendientes en la construcción de Antioquia. Además, este catálogo pretende ubicar en las manos del público, y de los especialistas en museos y en estética, el de-bate sobre las encrucijadas que encierra la representación museal de las obras artísticas y de las culturas de los pueblos afroamericanos fraguados en el seno de las dinámicas esclavistas, imperiales y coloniales.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Equivocation, Translation, and Performative Interseccionality: Notes on Decolonial Feminist Practices and Ethics in Latin America - de Lima Costa, Claudia (ANGLO SAXONICA, 2013)
In this paper I offer a brief overview of the academic debates about post-colonial theories and the concept of coloniality, seeking to map out their Latin American translations, especially from the perspective of feminist theories in relation to the coloniality of gender. By emphasizing an intersectional approach to understand the gendered character of coloniality, decolonial feminists are seeking innovative ways of articulating new epistemologies or “saberes propios”. However, in these debates little attention has been given to the issue of the travels and translations of decolonial feminisms in Latin America. In focusing on the vexed issue of translation, I want to explore some of the challenges Latin American decolonial feminists are facing today.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Memories of Underdevelopment: Art and the Decolonial Turn in Latin America, 1960-1985 - González, Julieta; Lerner, Sharon; Giunta, Andrea; Kanjo, Kathryn (Museum of Contemporary Art San Diego, 2018)
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Essay on Decolonial Aesthetics in Latin America - Luciano, Paula (RELACult - Revista Latino-Americana de Estudos em Cultura e Sociedade, 2019)
This essay aims to trace an overview of the decolonial aesthetics through the analysis of artistic expressions that occurred in Latin American territory. This analysis will allow us to enhance the cultural and artistic practices within its plurality and the typical spatial archetypes within its temporal resignification. The necessity of creation and the search for new epistemological fields translate the historical movements of the Latin-American cultural mouvance and the juxtaposition of temporalities, practices and the confluence of knowledge. We can find a stage of resistance and socio-historical borders subverted, mainly in the context of artistic and cultural manifestations and its capacity of invention and relativization. This essay aims to bring a reflection on the construction of cultural spaces and the dismantling of a single hegemonic perspective to define the artistic practices. The analysis and the epistemological questioning of the Latin-American trans-historical movement delineates an overview of the history of artistic productions that came out of practices and every-day life inventions and the elaboration of temporary spaces of claim and contestation through exhibitions, performances, festivals, and so forth. The idea of subverting a geopolitical imaginary and a cartography of the world (even if initially in local dynamics) consists of a central focus of this work.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Discursos sobre "raza" y nación en Colombia, 1880-1930 - Bendezú, Mauro Vega (Universidad del Valle, Facultad de Humanidades, Departmento de Historia, 2013)
Discursos sobre “raza” y nación en Colombia, 1880-1930 constituye un aporte a la investigación sobre la formación de la nación en Colombia durante los siglos xix al xx. El libro es producto de la investigación de tesis de maestría del autor y se centra en mostrar cómo las elites del país concibieron y, en específico, aplicaron con la legislación y otros recursos políticos y culturales, formas de poder y hegemonía mediante las cuales establecieron su dominio a partir del control social, la higienización -“depuración racial o blanqueamiento de la raza”- y el señalamiento a los grupos que resistieron esas formas arbitrarias de poder desde arriba. La estructura del libro está dividida en una introducción, cuatro capítulos, las conclusiones, la bibliografía y una corta semblanza del autor. El primer capítulo es un análisis metodológico de la “alteridad”, a partir de la perspectiva poscolonial y decolonial; siguiendo a autores de renombre en ese campo, trata de demostrar – lamentablemente de modo uniforme– el carácter cruel y violento del proceso de europeización y de sus valores “irracionales” más recurrentes. Los capítulos del dos al cinco se dedican a sustentar la postura metodológica con un material de fuentes y de análisis sobre el racismo colombiano en los siglos xix y xx.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Representaciones del espacio, el tiempo y las mujeres indígenas en fotografías, siglos XIX-XXI - Yujnovsky, Ines (Memoria y Sociedad, 2017)
Este trabajo se propone comprender la incidencia de las relaciones de poder que ciertas representaciones temporales acerca de grupos indígenas pueden ejercer en nuestra comprensión pasada y actual. Diversas imágenes reprodujeron ideas de indígenas que, aunque estuvieran vivos, mostraban una cultura asimilada a un pasado de amplias dimensiones. Por lo tanto, para comprender el proceso de invisibilización de la diversidad indígena en la cultura nacional, es relevante considerar los mecanismos de montaje discursivo —visuales y textuales—, vinculados con las nociones temporales de indios viviendo en un supuesto tiempo remoto. Atendiendo a ello, se analizan los procesos de montaje, desde la producción de las fotografías hasta la edición y presentación de imágenes, tanto en la prensa como en postales, publicaciones científicas y de divulgación, para ver cómo a veces pequeños cambios de encuadre, contraste, retoque o selección pueden incidir en la construcción de diversas historias, en la comprensión y en los sentidos construidos y en pugna.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

La temporalidad como política: nación, formas de pasado y perspectivas poscoloniales - Rufer, Mario (Memoria y Sociedad, 2010)
Este artículo discute el concepto de tiempo en la historia-disciplina como una noción política. A partir del análisis de las relaciones entre historia, nación y temporalidad, el autor intenta desentrañar por qué existe una distribución jerárquica de sujetos de la historia y sujetos de la cultura. Estudiando casos concretos de Sudáfrica y Argentina, intenta ver de qué manera esa distribución (incluso resignificada en la “nación multicultural”) impide ver ciertas continuidades en la reproducción de las asimetrías. El trabajo culmina analizando una noción poscolonial de historia como pérdida, como un regimen híbrido de historicidad. This article discusses the concept of time in History (the discipline) as a political notion. Starting with and analysis of the connivences between history, nation and temporality, the author tries to unravel why it operates a hierarchical distribution of “subjets of history” and “subjects of culture”. Dealing with specific cases of South Africa and Argentina, he tries to see how this distribution (even resignified in the “multicultural nation”) prevents to realize certain continuities in the reproduction of asymmetries. This piece of work ends analyzing a postcolonial notion of history as loss, meaning a hybrid regime of historicity.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Curar el pasado: teoría, curaduría y diálogo en una muestra de arte indígena contemporáneo del Gran Chaco Gualamba - Cantero, Emanuel (Memoria y Sociedad, 2018)
El siguiente artículo es una respuesta a la exposición de arte indígena contemporáneo Gran Chaco Gualamba. Arte, Cosmovisión, Soberanía (Chaco, Argentina; Julio de 2013). Sin desviarse de los propios objetivos de la muestra, problematiza la práctica curatorial como una forma de ver y mostrar a la producción artística de las poblaciones originarias como artefactos significantes íntimamente enlazados con sus formas de vida comunitaria -y no meramente obras de arte autónomas y asépticas de toda función social-. Contrastando las definiciones del equipo de curadoras, el corpus de obras expuestas y el discurso de pobladores originarios, se muestra que este intento por recuperar el nexo orgánico entre arte, cosmovisiones y vida en comunidad resulta trunco, dado que los propios pobladores originarios consideran esta vinculación como una circunstancia históricamente pretérita, previa a los procesos de colonización. Recuperando las luchas presentes de las comunidades, que a falta de ese pasado armonioso plantean su identidad como resistencia necesaria para un futuro distinto – mejor-. This work is a response to a contemporary indigenous art exhibition titled «Gran Chaco Gualamba - Arte, Cosmovisión, Soberanía» (Chaco, Argentina; July 2013). Consistent with the purposes of this exhibition, the article problematizes curatorial practice as a way to present the artistic production of the indigenous populations as significant artifacts intimately involved in the daily community life, and not merely as autonomous artistic objects with no social function. By contrasting the definitions provided by the curatorial team,the corpus of artworks exhibited and the native peoples’ speech, the article shows how the exhibit fails to recover the link between art, cosmovisions and community life because the native populations themselves consider these three spheres as an outdated historical circumstance, previous to the colonization processes. Finally, the current struggles of the communities are mapped which, in the absence of that harmonious past, pose their identity as a necessary resistance for a better future.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Imágenes de lo extraordinario. Memorias de un continente poblado por monstruos. - Gil, Slenka Leandra Botello; Camacho, Daianna Sierra (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este trabajo presenta los resultados de la investigación Imágenes de lo extraordinario: monstruos americanos del siglo XVI, proceso de creación artística desarrollado por los estudiantes del Semillero de Investigación en Artes Visuales (SINAV) del programa de Artes Visuales de la Universidad Nacional Abierta y a Distancia (UNAD) entre 2018 y 2019. Para analizar de manera crítica e histórica la construcción de identidades sobre lo latinoamericano, se tomó como marco de análisis la representación de lo monstruoso en los relatos y las imágenes construidas por los cronistas de Indias en el siglo XVI, los cuales marcaron procesos de marginalización cultural, construcción de subjetividades y dinámicas de poder, y presentaron al habitante americano como una otredad que estaba fuera de los límites de la cultura dominante occidental. Se presentan los postulados teóricos sobre lo monstruoso como marco para el análisis histórico y la creación de obra, con una metodología de trabajo colaborativo y en gran parte virtual. Posteriormente, se exponen algunos resultados de la investigación histórica que dan paso a detallar el proceso de creación de obra que culminó con la exposición de la instalación audiovisual Imágenes de lo extraordinario, así como con una amplia serie de ilustraciones contemporáneas sobre lo monstruoso y un producto digital en formato página web donde se presenta una cartografía de lo monstruoso en América Latina y se recogen las memorias de todo el proyecto. This work presents the results of the research Images of the Extraordinary: American Monsters of the 16th Century, artistic creation process developed by the students of the Research Seedbed in Visual Arts (SINAV, for its initials in Spanish) of the Visual Arts program of Universidad Nacional Abierta y a Distancia (UNAD) between 2018 and 2019. With the objective of analyzing, in a critical and historical way, the construction of identities on Latin American matters, the representation of the monstrous in the stories and images constructed by the chroniclers of the Indies in the 16th century was used as a framework of analysis. These chroniclers marked processes of cultural marginalization, construction of subjectivities and power dynamics, and presented the American inhabitant as an otherness that was outside the limits of the dominant Western culture. The theoretical postulates about the monstrous are presented as a framework for historical analysis and the creation of works, with a collaborative and largely virtual working methodology. Some results of the historical research are then presented, which gives way to detailing the process of creating work that culminated in the exhibition of the audiovisual installation Images of the Extraordinary, as well as a wide range of contemporary illustrations on the monstrous and a digital product in web page format where a cartography of the monstrous in Latin America is presented and the memories of the whole project are collected.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Memorias americoafricanas en el trabajo de artistas brasileñas contemporáneas - Sardelich, Maria Emilia; Cao, Marian López Fernandez (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
La memoria hace referencia a un conjunto de funciones psíquicas que permiten la actualización de imágenes de hechos pasados o que se representan como pasados. A diferencia de los estudios históricos, los de la memoria resaltan las subjetividades, amplían la discusión más allá del recuerdo y el olvido, y desplazan el debate hacia quien tiene el derecho a narrar su historia y aquellos que en ella se encuentran. Las inquietudes en torno a la memoria y sus lugares también se hacen visibles en el inquieto horizonte artístico, en el que pasados recientes y distantes se articulan en registros sobre diversas formas de traumas. Este artículo propone una reflexión sobre las relaciones entre arte y memoria a partir de la producción de dos artistas brasileñas contemporáneas: Rosana Paulino (São Paulo, 1968) y Aline Motta (Niterói, 1974). El análisis de esa producción se fundamenta en la interdisciplinaridad de los estudios de la memoria y destaca cómo la creación artística ofrece una posibilidad de resignificación individual y colectiva. Asimismo, conceptúa memorias americoafricanas como aquellas que emergen no solo en la memoria individual de las artistas presentadas en este artículo, sino también en la de muchas otras mujeres que se identifican con Americoáfrica como un sistema etnogeográfico de referencia. Son memorias americoafricanas porque se han gestado en la resistencia y creatividad contra la opresión, la humillación y la deshumanización, y que se insurgen contra la historia única proponiendo una revisión de la historiografía del país y del arte producido a partir de esos lugares. Memory refers to a set of psychic functions that allow the updating of images of past events or events that are represented as past. Unlike historical studies, memory studies highlight subjectivities, expand the discussion beyond memory and oblivion, and shift the debate towards who has the right to narrate their history and those who are in it. The concerns about memory and its places also become visible in the restless artistic horizon, in which recent and distant pasts are articulated in registers about various forms of trauma. This paper proposes a reflection on the relationship between art and memory based on the production of two contemporary Brazilian artists: Rosana Paulino (São Paulo, 1968) and Aline Motta (Niterói, 1974). The analysis of this production is based on the interdisciplinary nature of memory studies and highlights how artistic creation offers a possibility of individual and collective resignification. Likewise, it conceptualizes African-American memories as those that emerge not only in the individual memory of the artists presented in this article, but also in that of many other women who identify with Africa-America, as a reference ethnogeographic system. They are African-American memories because they have been born in resistance and creativity against oppression, humiliation and dehumanization, and because they insurrect against the unique history, proposing a review of the historiography of the country and the art produced out of those places.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

“Tu vida también es mi país”: sexualidades disonantes y fugas de género en Liliana Felipe y Jesusa Rodríguez - Muelle, Camila Esguerra; Martínez, Alejandra Quintana (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2018)
Este artículo propone una reflexión sobre las prácticas vitales, artísticas y políticas de Liliana Felipe y Jesusa Rodríguez y sus experiencias de desobediencia frente a los regímenes de sexualidad y género articulados a regímenes de terror en México y Argentina. La metodología usada para llegar a la reflexión fue un análisis crítico multimodal del discurso hecho desde una perspectiva interseccional y descolonial que supone el análisis tanto de contextos como de los textos, subtextos y texturas que componen la obra y vida de estas artistas. Desde esta postura epistemológica, la obra performática y musical de Liliana y Jesusa es vista como un acervo de discursos multimodales. Nuestra reflexión muestra cómo la creación, la experiencia —entendida como lugar político— y las propuestas colectivas de Liliana y Jesusa se ponen en juego en un campo de lucha performativa donde sus discursos desobedientes proponen maneras de resistencia y fuga a los regímenes coloniales-modernos- capitalistas de género y sexualidad. Jesusa y Liliana proponen una obra multimodal y multimedial que fisura los límites de los géneros discursivos, los géneros musicales, el género gramatical y el sistema sexo género, lo cual amerita una mirada indisciplinada. Este artículo resulta ser un abordaje novedoso en la medida en que se acerca a la experiencia y a la obra de estas dos mujeres, no desde una visión disciplinar, sino a partir de una mirada transdisciplinaria, interseccional y descolonial que asume la producción artística como una apuesta política donde los límites entre lo personal y lo público se borran. This article seeks to do a reflection both on the vital, artistic and political practices of Liliana Felipe and Jesusa Rodríguez and on their experiences of disobedience to the regimes of sexuality and gender, which are articulated to regimes of terror in Mexico and Argentina. The methodology used in order to make this reflection was a Multimodal Critical Discourse Analysis from both an intersectional and decolonial perspective. This methodology implies the analysis of contexts, texts, subtexts and textures that make up the work and life of these artists. From this epistemological position, the performative and musical work of Liliana and Jesusa is seen as a collection of multimodal discourses. Creation, experience —understood as a political locus— and the collective proposals of Liliana and Jesusa are put into play in a field of performative struggle where their disobedient discourses propose ways of resistance to colonial-modern-capitalist regimes of gender and sexuality.Jesusa and Liliana propose a multimodal and multimedial work that fissures the limits of the discursive genres, the musical genres, the grammatical gender and the gender sex system, which deserves an undisciplined look. This article proposes an original approach insofar as it approaches the experience and work of these two women not from a disciplinary view, but from a transdisciplinary, intersectional and decolonial point of view, that assumes artistic production as a political commitment in where the boundaries between the personal and the public are erased.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé

Procesos de invención decoloniales sobre visualidades indígenas. Hacia una reconfiguración de los imaginarios hegemónicos en el nordeste argentino - Reyero, Alejandra; Navas, Maia (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
El objetivo del artículo es discutir la potencialidad de prácticas artísticas contemporáneas que plantean ejercicios decoloniales al desestabilizar las matrices perceptivas eurocéntricas sobre grupos étnicos latinoamericanos. Desde la perspectiva de los estudios visuales, aborda la tentativa de demolición crítica de la cultura visual y los regímenes de visibilidad regidos por la lógica de la hipercomunicación y las tecnologías digitales. El punto de partida es el análisis del videoensayo Ashipegaxanacxanec iniciado en 2020 a partir de las acciones de control implementadas en la pandemia de covid-19. La producción se inscribe en las líneas de investigación del Núcleo de Estudios y Documentación de la Imagen (Nedim), Conicet-UNNE, con la finalidad de resignificar el acervo fotográfico del antropólogo alemán Lehmann Nitsche obtenido en el contexto de la masacre indígena en la Reducción de Napalpí, Chaco, en 1924. Metodológicamente, la propuesta explora la configuración experiencial de visualidades expandidas en la escena contemporánea, a partir de un anclaje en la dimensión especulativa en sintonía con un acercamiento contextual situado en las relaciones de convergencia entre pro- cedimientos, materiales, formatos, dispositivos e instancias disruptivas de prácticas y trayectorias estéticas. Ello supone la activación de procesos heurísticos y poéticos mediados por el ensayo y la escritura como montaje. Propuestas como el videoensayo analizado instauran la pregunta por el archivo y la memoria a través del montaje de temporalidades contradictorias. Su lugar de enunciación se posiciona como posibilidad de insurgencia estética que clausura tentativas de exotización hegemónica por parte de los dispositivos de control contemporáneos. The goal of this paper is to discuss the potentiality of contemporary artistic prac-tices that propose decolonial exercises by destabilizing the Eurocentric perceptual matrices on Latin American ethnic groups. From the perspective of visual studies, it addresses the attempt to critically demolish visual culture and the regimes of visibility governed by the logic of hypercommunication and digital technologies. The starting point is the analysis of the Ashipegaxanacxanec video essay started in 2020 based on the control actions implemented in the COVID-19 pandemic. The production is part of the research of the Image Studies and Documentation Center (Nedim), Conicet-UNNE, with the purpose of redefining the photographic collection of German anthropologist Lehmann Nitsche, obtained in the context of the indigenous massacre in the Napalpí reduction in Chaco, in 1924. Methodologi-cally, the proposal explores the experiential configuration of expanded visualities in the contemporary scene, based on an anchoring in the speculative dimension in tune with a contextual approach in the convergence relationships between proce-dures, materials, formats, devices and disruptive instances of practices and aes-thetic trajectories. This supposes the activation of heuristic and poetic processes mediated by essays and writing as montage. Proposals such as the analyzed video essay establish the question about the archive and memory through the montage of contradictory temporalities. Its place of enunciation is positioned as a possibili-ty of aesthetic insurgency that closes any attempts at hegemonic exoticization by contemporary control devices
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

Shekuita o el mal trueno: documental performativo, conflictos ontológicos y descolonización de lo real - Rincón, Juan Carlos Valencia; Hoyos, Paula Andrea Restrepo (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este artículo analiza las implicaciones ontológicas y el carácter performativo del documental Shekuita o el mal trueno, lanzado en 2017 por un colectivo de producción audio- visual indígena wiwa en la Sierra Nevada de Santa Marta en Colombia. El documental explora las causas, dudas y consecuencias de un triste incidente ocurrido tres años antes: la caída de un rayo sobre una edificación ceremonial de los wiwas, que causó la muerte a casi una docena de líderes. A partir del contraste entre las explicaciones científicas de la tragedia y las que han investigado las autoridades espirituales de la comunidad desde sus ontologías relacionales, y basándonos en un trabajo de campo cuasietnográfico durante el proceso de filmación, buscamos dar cuenta de un caso específico de descolonización de lo real y de los esfuerzos de una comunidad indígena por la libre expresión y la representación autónoma. Encontramos que este documental abre puertas de forma artística a mundos otros, contados en clave insumisa desde una indigenidad que nos interpela. Concluimos que los wiwas performan un realidad que no necesariamente es la que vivieron, sino una que les permite estratégicamente alcanzar más fácilmente la realidad que quieren recuperar. El artículo intenta contribuir a la visibilización de otras ontologías distintas de la naturalista, a mostrar las autocríticas de esta y a manifestar cómo el audiovisual es un espacio propicio para descolonizar lo real. This paper analyzes the ontological implications and the performative nature of the documentary Shekuita o el mal trueno, released in 2017 by a Wiwa indigenous audiovisual production group in Sierra Nevada de Santa Marta, Colombia. The do-cumentary explores the causes, doubts and consequences of a sad incident that happened three years earlier: a lightning strike on a Wiwas ceremonial building, which killed nearly a dozen leaders. Based on the contrast between the scientific explanations of the tragedy and those that the spiritual authorities of the community have investigated according to their relational ontologies and based on a quasi-eth-nographic fieldwork during the filming process, we seek to account for a specific case of decolonization of reality and of the efforts of an indigenous community for free expression and autonomous representation. We find that this documentary opens doors to other worlds in an artistic way, told in an unsubmissive way by an indigenous community that challenges us. We conclude that the Wiwa perform a reality that is not necessarily the one they lived through, but one that strategically allows them to reach the reality they want to recover more easily. The paper at-tempts to contribute to the visibility of other ontologies other than the naturalistic one, to show self-criticism of it and to show how the audiovisual is a propitious space to decolonize reality.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Genealogías críticas de la colonialidad en América Latina, África, Oriente - Segato, Rita Laura, [et al.] (Universidad Nacional de San Martín, 2016)
El espesor de este libro es propio de este tiempo. Cuerpos que se desplazan en masivas inmigraciones huyendo de todo tipo de violencias alcanzan a más de sesenta millones de personas, la mayor cifra de refugiados desde la segunda guerra mundial. El mundo experimenta una crisis humanitaria sobrecogedora ante la cual las potencias apelan a los mismos discursos que ya Aimé Césaire o Fanon condenaran. Dramatismo del exilio de este nomadismo a escala planetaria, al cual Stuart Hall calificaría como “amensia imperial”. Genealogías críticas de la colonialidad en América Latina, África, Oriente es un libro que deja al descubierto la piel del mundo contemporáneo. Un hecho cultural disruptivo que, anudado a una genealogía latinoamericana abierta a sí misma y hacia Otros Sures se interroga sobre los intrincados modos de narrar y silenciar los pasados coloniales.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Coloniality of Power, Eurocentrism, and Latin America - Quijano, Anibal (Nepantla: Views from South, 2000)
What is termed globalization is the culmination of a process that began with the constitution of America and colonial/modern Eurocentered capitalism as a new global power. One of the fundamental axes of this model of power is the social classification of the world’s population around the idea of race, a mental construction that expresses the basic experience of colonial domination and pervades the more important dimensions of global power, including its specific rationality: Eurocentrism. The racial axis has a colonial origin and character, but it has proven to be more durable and stable than the colonialism in whose matrix it was established. Therefore, the model of power that is globally hegemonic today presupposes an element of coloniality. In what follows, my primary aim is to open up some of the theoretically necessary questions about the implications of coloniality of power regarding the history of Latin America.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Marta Rodríguez, descolonizando la representación documental latinoamericana - Moreno, Pedro Pablo Gómez (Estudios Artísticos, 2017)
En esta conversación entre la cineasta documental Marta Rodríguez y Pedro Pablo Gómez, antes que hacer un recorrido cronológico por el trabajo la artista, se abordan problemas tranversales que están presentes a lo largo de su obra: el cine documental como modo de representación; la construcción de una metodología del cine documental latinoamericano; el carácter decolonial de la obra de Rodríguez y su compromiso indeclinable durante más de cuatro décadas de acompañar las luchas de campesinos, indígenas y afrodescendientes, entre otros. Y es en este abordaje donde Marta Rodríguez, haciendo uso de una memoria extraordinaria, puede tejer un relato en el que se destaca la ética de la artista y su compromiso indeclinable de denuncia de las injusticias sociales, utilizando las tecnologías del cine, no para hablar por las víctimas, sino para hacer escuchar sus voces y mantener vivas sus imágenes; unas imágenes que interpelan el discurso colonial mediante el cual se ha tejido nuestro relato de nación. Dans cette conversation entre la cinéaste documentaire Marta Rodríguez et Pedro Pablo Gómez, avant d'entreprendre une tournée chronologique de l'œuvre de l'artiste, nous traitons les problèmes transversaux présents tout au long de son travail : le cinéma documentaire comme mode de représentation ; la construction d'une méthodologie du documentaire latino-américain; la nature décoloniale de l'œuvre de Rodríguez et son engagement pendant plus de quatre décennies pour accompagner les luttes des paysans, des indigènes et des Afro-descendants, entre autres. Et c'est dans cette approche que Marta Rodríguez, avec une mémoire extraordinaire, peut tisser une histoire qui souligne l'éthique de l'artiste et son engagement indécelable à dénoncer les injustices sociales, en utilisant les technologies du cinéma –pour ne pas parler en lieu des victimes, mais pour faire entendre leur voix et garder leurs images vivantes. Des images qui contestent le discours colonial par lequel notre récit de nation a été tissé.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créatrice; _Nettoyé

“Estética(s) decolonial(es)1”: entrevista a Pedro Pablo Gómez - Vasquez, Angélica González; Zacarias, Gabriel Ferreira (Estudios Artísticos, 2016)
En esta conversación se indaga por la cuestión decolonial de la estética, sus puntos de origen históricos y geográficos, además de sus posibilidades en el contexto de reconfiguración actual del orden mundial. Desde esta perspectiva, se pretende aclarar en qué consiste la opción decolonial, respecto de otras opciones, sin olvidar cuestiones importantes del arte, la historia, el museo, la curaduría y sus implicaciones éticas, políticas y epistémicas. Cette conversation touche à la question de l’esthétique décoloniale, de ses points d’origine historiques et géographiques et de ses possibilités dans le contexte de la reconfiguration actuelle de l’ordre mondial. Dans cette perspective, l’objectif est de clarifier l’option décoloniale par rapport à d’autres options — sans oublier les questions importantes de l’art, de l’histoire, des musées, de la mission du curateur — et ses implications éthiques, politiques et épistémiques.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

La relación: pauta epistémica de la decolonialidad del saber desde el pensamiento afroantillano Los contornos del concepto en el Tratado del Todo-Mundo de Édouard Glissant (1928-2011) - Juncosa, José Enrique (Estudios Artísticos, 2016)
El presente artículo rastrea y explora el sentido poético y las posibilidades epistémicas del término relación a partir de la obra Tratado del todo-mundo, de Édouard Glissant, asumida como aporte del pensamiento afroantillano al proyecto del giro decolonial de los estudios interculturales latinoamericanos. En un primer momento, se identifican los rasgos y contornos operatorios de la identidad relación a partir de las siguientes claves de lectura: imaginería, poética y retórica, espiritualidad y ética, política y epistémica. En el segundo momento, se identifican las conexiones e implicaciones más relevantes para el contexto andino. De la exploración, se desprende que el pensamiento afrocaribeño de Glissant, contribuye a generar posibilidades discursivas potentes para enriquecer identidades abiertas en su diferencia y prácticas epistémicas sin amurallamientos identitarios o ilusiones uniformizantes. Finalmente, el aporte de Glissant, ofrece espacios de búsquedas a los movimientos sociales andinos para enriquecer sus prácticas de identidad en tanto relación, más allá de los esencialismos y la pretensión de raíz única. Cet article retrace et explore le sens poétique et les possibilités épistémiques du terme relation dans le traité d’Édouard Glissant, Traité du Tout-Monde, en tant que contribution afro-antillaise au projet du virage décolonial dans les études interculturelles latino-américains. Premièrement, nous identifions les traits et les contours opératoires de l›identité relationnelle à partir de clés suivantes : imagerie, poétique et rhétorique, spiritualité et éthique, politique et épistémique. Les liens les plus pertinents et les implications pour le contexte andin sont alors identifiés. De cette exploration, il est clair que la pensée afro-antillaise de Glissant contribue à générer de puissantes possibilités discursives pour enrichir des identités ouvertes dans leurs différences et leurs pratiques épistémiques, sans de murs identitaires ni d’illusions normalisatrices. Enfin, la contribution de Glissant ouvre des espaces de recherche pour les mouvements sociaux andins afin d’enrichir leurs pratiques d’identité en tant que relation, au-delà des essentialismes et de la prétention d’une seule origine.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

Imaginarios y estrategias decoloniales - Ferrera-Balanquet, Raúl Moarquech (Estudios Artísticos, 2018)
Enunciando el delinking de la matriz moderna/ colonial, este artículo imagina un territorio crítico teórico creativo partiendo de la aesthesis decolonial con el fin de dialogar con una serie de hacedores culturales que emplean estrategias creativas decoloniales en proyectos creativos. Un acercamiento a la exposición Haceres Decoloniales (2015) realizada en Bogotá, ofrece la oportunidad de conversar sobre el hacer creativo de Benvenuto Chavajay, Rosa Tisoy Tandoy y Marco Alonso Roa. Los efectos de la colonialidad sonora conllevan a dialogar con la artista maya k´iche Sandra Monterroso y el creador maya yucateco Isaac Carrillo Can. Discursamos sobre el proyecto Espejo Negro (2010) de Pedro Lasch y el mural Las Aguas Sagradas de La Llorona (2004) de la artista xicana Juana Alicia. Terminamos con una interpretación crítica sobre el proyecto Mariposa Memoria Ancestral (2013-2015), y el performance multidisciplinario Whip It Good (2013) de la artista danesa trinitobaguense Jeannette Ehlers. En reliant la déconnexion de la matrice moderne / coloniale, cet article imagine un territoire créatif- théorique-critique à partir de l’aesthésis décoloniale, afin de dialoguer avec une série d’acteurs culturels qui utilisent des stratégies décoloniales créatives dans des projets créatifs. Une approche de l’exposition Haceres Decoloniales (2015) tenue à Bogotá, offre l’occasion de parler du travail créatif de Benvenuto Chavajay, Rosa Tisoy Tandoy et Marco Alonso Roa. Les effets de la colonialité sonore impliquent un dialogue avec l’artiste maya k’iche Sandra Monterroso et le créateur maya yucatècque Isaac Carrillo Can. Nous parlons du projet Espejo Negro (2010) de Pedro Lasch et de la peinture murale Las Aguas Sagradas de La Llorona (2004) de l’artiste chicane Juana Alicia. Nous terminons avec une interprétation critique du projet Mariposa Memoria Ancestral (2013-2015) et la performance pluridisciplinaire Whip It Good (2013) de l’artiste danois né en Trinité-et-Tobago Jeannette Ehlers.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave games in context, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Fotografía Latinoamericana Contemporánea: crítica poscolonial y renovación de los lenguajes. El caso de Brasil. - Rigat, Leticia (Revista Crítica Cultural, 2018)
En el presente trabajo nos proponemos reflexionar sobre el surgimiento de la categoría Fotografía Latinoamericana hacia fines de la década del setenta. Una reflexión sobre las prácticas fotográficas que refleja un intento de descolonizar las definiciones y categorías sobre la fotografía realizada en América Latina.Desde aquel momento, se estableció un concepto que englobaba bajo una misma rúbrica la fotografía latinoamericana y la representación del Ser latinoamericano, su identidad y su historia compartida en las diferentes naciones de la región. Una definición que cambia en los años noventa donde puede observarse una renovación de los modos de representación que complejizan las miradas sobre el pasado colonial y la heterogeneidad de nuestras identidades.Tras el análisis general de la búsqueda de definir una práctica cultural desde una perspectiva poscolonial de la fotografía latinoamericana, buscaremos centrarnos en el caso de la fotografía brasileña en dicho período.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Coloniality at Large: Latin America and the Postcolonial Debate - Moraña, Mabel; Dussel, Enrique; Jáuregui, Carlos A. (Duke University Press, 2008)
Postcolonial theory has developed mainly in the U.S. academy, and it has focused chiefly on nineteenth-century and twentieth-century colonization and decolonization processes in Asia, Africa, the Middle East, and the Caribbean. Colonialism in Latin America originated centuries earlier, in the transoceanic adventures from which European modernity itself was born. Coloniality at Large brings together classic and new reflections on the theoretical implications of colonialism in Latin America. By pointing out its particular characteristics, the contributors highlight some of the philosophical and ideological blind spots of contemporary postcolonial theory as they offer a thorough analysis of that theory’s applicability to Latin America’s past and present. Written by internationally renowned scholars based in Latin America, the United States, and Europe, the essays reflect multiple disciplinary and ideological perspectives. Some are translated into English for the first time. The collection includes theoretical reflections, literary criticism, and historical and ethnographic case studies focused on Ecuador, Guatemala, Mexico, Brazil, the Andes, and the Caribbean. Contributors examine the relation of Marxist thought, dependency theory, and liberation theology to Latin Americans’ experience of and resistance to coloniality, and they emphasize the critique of Occidentalism and modernity as central to any understanding of the colonial project. Analyzing the many ways that Latin Americans have resisted imperialism and sought emancipation and sovereignty over several centuries, they delve into topics including violence, identity, otherness, memory, heterogeneity, and language. Contributors also explore Latin American intellectuals’ ambivalence about, or objections to, the “post” in postcolonial; to many, globalization and neoliberalism are the contemporary guises of colonialism in Latin America. Contributors : Arturo Arias, Gordon Brotherston, Santiago Castro-Gómez, Sara Castro-Klaren, Amaryll Chanady, Fernando Coronil, Román de la Campa, Enrique Dussel, Ramón Grosfoguel, Russell G. Hamilton, Peter Hulme, Carlos A. Jáuregui, Michael Löwy, Nelson Maldonado-Torres, José Antonio Mazzotti, Eduardo Mendieta, Walter D. Mignolo, Mario Roberto Morales, Mabel Moraña, Mary Louise Pratt, Aníbal Quijano, José Rabasa, Elzbieta Sklodowska, Catherine E. Walsh
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); _Nettoyé

Hacia una memoria decolonial: breves apuntes para indagar por el acontecimiento detrás del acontecimiento fotográfico - Schlenker, Alex (Revista de Investigación en el Campo del Arte, 2012)
El retrato ha sido, a lo largo de la historia de la fotografía, un ritual cuya gramática visual está siempre condicionada por una mirada determinada. Retratamos para recordar, para fijar un instante en el tiempo. Cuando recordamos lo fotografiado convocamos de nuevo ese instante, pero, además, convocamos una realidad, un orden social específico construido por determinados actores sociales. La fotografía ha representado y legitimado en muchos momentos un patrón de poder colonial que, a través de sus estructuras de dominación, ha elaborado rígidas jerarquías sociales y raciales que han circunscrito a indios, afros, mujeres y clases populares a lo que Frantz Fanon llama la zona del No-ser. ¿Es posible recordar, entonces, a partir de la fotografía, de manera crítica y sin reproducir en tal ejercicio la matriz colonial que hizo posible la toma de la imagen?
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Por uma pedagogia crioula : memória, identidade e resistência no quilombo de Conceição das Crioulas – PE - Nascimento, Márcia Jucilene do (Universidade de Brasília, 2017)
This dissertation aims to describe the specific schooling process developed in the quilombo of Conceição das Crioulas, in Salgueiro / PE. This process was a result of the socio-historical reconstruction movement of the quilombo’s history, which started in the 1980s. This process triggered several conflicts, and priority was given to the regaining of their territory and to the search for educational practices with decolonizing ideals. Based on the individual and collective memories of Conceição das Crioulas people, we have registered the historical accounts of the community’s resistance to the domination and oppression systems imposed to them since the arrival of the creole founders until today. The methodological trajectory was based on interviews, informal conversations and the analysis of a video-documentary, specifically recorded for this research. This path also allowed us to evaluate how we have perceived and done our school education over a period of twenty-two years, whose milestone is the inauguration, in 1995, of Professor José Mendes school, a local public school where grades 6th to 9th are taught. First, this paper addresses important elements for the beginning of this search. Next, it describes practices and specific actions of the education of Conceição das Crioulas. After that, it draws a comparative analysis about this and other pedagogical experiences, highlighting connections and significant distances between them. Finally, at the end of the last chapter, it conceptualizes this experience, which was named Crioula Pedagogy in the community.
Keywords: 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice noir.e; _À analyser

Feminist Geographies in Latin America: Epistemological Challenges and the Decoloniality of Knowledge - Silva, Joseli Maria; Ornat, Marcio Jose (Journal of Latin American Geography, 2020)
This paper analyzes the growth of gender studies in Latin America, despite facing resistance in the scientific field and from the advance of conservative policies on the continent. It also addresses the challenges that feminist research faces in colonized spaces. To develop our argument, we draw on the scholarship of feminist researchers in Brazil, Mexico, and Argentina, such as Veleda da Silva and Lan (2007), Silva and Vieira (2014), Silva, César and Pinto (2015), Colombara (2016), Lan (2016), Veleda da Silva (2016), Ibarra-García and Escamilla-Herrera (2016), Zaragocin-Carvajal, Moreano-Venegas, and Álvarez-Velasco (2018), and Silva and Ornat (2019). This paper also examines the difficulties that Latin American feminist geographies face in establishing their own foundations in a globalized world where the geopolitics of global knowledge of geography is increasingly structured by the epistemological centralization of the Anglophone northern hemisphere.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé

The Postcolonial in Latin America and the Concept of Coloniality: A Historian’s Point of View - Salvatore, Ricardo D. (A Contracorriente: una revista de estudios latinoamericanos, 2010)
Discussion of Coloniality at Large: Latin America and the Postcolonial Debate (Durham, NC and London: Duke University Press, 2008) by Mabel Moraña, Enrique Dussel, and Carlos A. Jauregui (eds.).
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Hacia una reapropiación de la geografía crítica en América Latina. - Zaragocin-Carvajal, Sofía; Moreano-Venegas, Melissa; Álvarez-Velasco, Soledad (Íconos. Revista de Ciencias Sociales, 2018)
This article attempts to review and synthesise the main debates in critical geography across both the Latin American and Anglo-Saxon traditions. By reviewing the main theoretical approaches including from political ecology, feminist geography, post-colonial and de-colonial approaches and the geography of motilities and migration, the aim of this article is to delineate a pan-Latin American approach to critical geography. We also consider why some approaches and topics have received greater or lesser attention in Latin American scholarship. Finally, we emphasize the importance of establishing a new transnational dialogue based on regionally situated critical research that questions and proposes new pathways in the production of knowledge from and about the region. We suggest this approach be nested in critical theory and committed to local political and territorial struggles.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

El giro decolonial: reflexiones para una diversidad epistémica más allá del capitalismo global - Castro-Gómez, Santiago; Grosfoguel, Ramón (Siglo del Hombre Editores, 2007)
Este libro reúne ensayos de doce teóricos latinoamericanos, quienes hacen una reflexión acerca de la diversidad epistémica en el mundo contemporáneo. Plantean que la decolonialidad en el siglo XXI tendrá que dirigirse a la heterarquía de las múltiples relaciones raciales, étnicas, sexuales, económicas y de género que quedaron intactas durante el siglo XX.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

“Estrategia ARTNIVORA” Estéticas decoloniales, antropofagia y la construcción de una mirada crítica para las artes visuales en América Latina - López Jaramillo, David Andrés (Universidad Andina Simón Bolívar, 2016)
Este trabajo trata sobre artes visuales modernas y contemporáneas en América latina. Como ejes trasversales del texto se plantea: la decolonialidad y la antropofagia crítica. Parte desde la problematización de las estéticas decoloniales y la revisión histórica del arte latinoamericano del siglo XX, primero modernista luego posmoderno, desde una aproximación decolonial. Su intención es analizar si la opción decolonial es viable para artes visuales. Pretende analizar la propuesta de la decolonialidad, así como sus límites y sus principales riesgos. Además de establecer puentes con la ética posmoderna y la ética latinoamericana. En el capítulo dos trata como eje principal la antropofagia, tanto como movimiento artístico moderno, como propuesta de producción y aproximación crítica, cultural y artística. Mira a la antropofagia como proceso y como metodología posmoderna de resistencia. Bajo estos parámetros analiza la obra de tres artistas modernistas latinoamericanos: Joaquín Torres García, Tarsila do Amaral y Wilfredo Lam. Luego, y a partir de esta aproximación, en el capítulo tres se plantea el análisis crítico a una práctica artística: la muestra ARTNIVORA (2011) del colectivo femenino de arte La emancipada en Quito. Analiza en esta muestra, como el colectivo emplea la antropofagia crítica para buscar un argumento de emancipación de género. En esta muestra de arte actual, las estrategias de la apropiación y la cita contemporáneas son leídas como una práctica antropofágica. La intención es presentar un diferente punto de vista para la producción y la apreciación de las artes visuales y plásticas contemporáneas latinoamericanas, tanto obras de arte, como el trabajo creativo y los procesos de sus autores y autoras. El texto plantea la importancia del sentido de pertenencia con la localidad en la expresión de arte visual, si bien emplea un lenguaje cuyos códigos pueden ser leídos internacionalmente, su anclaje es su localidad y problemáticas insertas en un contexto local.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Una lectura postpornográfica de Roberto Bolaño: escritura, feminismo y postcolonialismo - Rodríguez, Josué Hernández (Moderna språk, 2021)
The proliferation of critical and creative post-porn movements, which vindicate the representation of dissident sexualities under a new feminist, queer and transgender perspective, provide tools of analysis to rethink past literary and audiovisual pornographic productions, as well as to reformulate current ones. In this line of intermediate research, between cinema and literature, an approach to the work of Chilean writer Roberto Bolaño is proposed that will allow us to discern whether he can be considered a post-porn author related to the Golden Age of pornographic cinema in the 1970s and 1980s. Two of his stories and a novel will be studied: “Joanna Silvestri”, from which a gender reading will be made that problematizes the role of women within an eminently heteronormative industry, obsessed with representing male ejaculation; “Prefiguración de Lalo Cura”, analyzed under a postcolonial perspective of appropriation of subaltern bodies conceived as geographical territories, and Una novelita lumpen, in the field of porn pedagogy. The resulting findings make it possible to establish that Roberto Bolaño can indeed be considered a post-porn author by translating the narrative proposals of the Golden Age porn films into his own literary project, with a feminist and post-colonial critical intention.
Keywords: 2-Approches sociologiques; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir)

Imágenes decoloniales sobre la complejidad cultural - Lucero, Maria Elena (Revista SURES, 2015)
La producción visual de América Latina del siglo XX condensa una variable de emergentes artísticos diversosno solo por la complejidad histórica que caracteriza al continente sino por la pluralidad de comunidades nativas que conformaron su territorio geográfico. Así como la crítica cultural ha abonado fuertemente el terreno de las artes también han surgido otras vías de estudio enlazadas con dimensiones sociales, económicas y políticas. Cabe mencionar los aportes al ámbito de las producciones visualesde una perspectiva analítica que en el escenario latinoamericano se inscribe en el llamado ‘giro decolonial’. América Latina posee una tradición franqueada por luchas contra el colonialismo y el eurocentrismo. En la actualidad, la esfera artística contemporánea manifiesta sus posicionamientos colectivos frente a una sociedad globalizada. En este aspecto, las contribuciones de la inflexión decolonial permiten pensar otros sentidos inherentes a las formulaciones estéticas surgidas en estas regiones. Se analizarán las obras de Alfredo Jaar, Tania Bruguera y Milagros de la Torre.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Modernidad artística y giro decolonial - Rueda, María de los Ángeles De; Guzmán, Gerardo (Arte e Investigación Revista Científica de la Facultad de Bellas Artes, 2018)
Se trata de revisar las concepciones canónicas de la modernidad artística latinoamericana desde una perspectiva crítica y situada desde los estudios decoloniales y el hacer en las cátedras Historia de las Artes Visuales III e Historia de la Música III de la Facultad de Bellas Artes de la Universidad Nacional de La Plata. En ambas materias se trabajan contenidossobre las artes locales, nacionales y latinoamericanas/sudamericanas, en comparación conlos movimientos europeos de la modernidad y la contemporaneidad. Este proyecto revisa algunas líneas historiográficas recientes sobre la historia y la teoría de las artes locales ylatinoamericanas. Se revisarán, también, algunos casos de producciones artísticas.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

El lugar del arte en la opción por una desobediencia epistémica decolonial // The place of art in the option for decolonial epistemic disobedience - Bolaños, Martin (Hermeneutic : Revista Digital de Arte, Crítia y Filosofía, 2020)
The visualization of the ways of doing what is sensible in a globalized society is one more form of discipline of sensitivity and its poetics. The border between a colonized sensibility and an insurgent sensibility becomes blurred as the international distribution of the sensible assigns specific ways capable of domesticating the sensibilities that overwhelm it. Those sensitivities not that cannot be captured neither as merchandise, nor as an archive, nor as heritage. The overflow and excess of these sensitivities that have not been caught in the networks of an international art market jeopardize, by their very existence, the categories that aesthetics, as a modern-colonial discipline has produced to conceptualize and codify the sensitivities (isolationism) neutralized their capacities to witness historically subjugated life experiences. In this sense, decolonial stasis retrace the traced path, and one of the ways of retracing is to disarticulate or at least resignify words such as "art", "artist", "work", "production", "aesthetic", or "Poetic", among others.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); _Nettoyé

Beyond the Favela, the Rua and the Museum: Reading Hélio Oiticica and Artur Barrio from Decoloniality. Fluctuations and Paradoxes of a Latin-American Modernity - Lucero, María Helena (Southern Perspectives)
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Autrice; _Nettoyé